Where are children active and does it matter for physical activity?: A latent transition analysis - Colabianchi, Natalie (J Phys Act Health, 2016)
BACKGROUND: Numerous studies have focused on the role of environments in promoting physical activity, but few studies have examined the specific locations where children are active and whether being active in these locations is associated with physical activity levels over time. METHODS: Self-reported locations of where physical activity occurred and physical activity measured via accelerometry were obtained for a cohort of 520 children in 5(th) and 6(th) grades. Latent class analysis was used to generate classes of children defined by the variety of locations where they were active (i.e., home, school grounds, gyms, recreational centers, parks or playgrounds, neighborhood, and church). Latent transition analyses were used to characterize how these latent classes change over time and to determine whether the latent transitions were associated with changes in physical activity levels. RESULTS: Two latent classes were identified at baseline with the majority of children in the class labeled as ‘limited variety’. Most children maintained their latent status over time. Physical activity levels declined for all groups, but significantly less so for children who maintained their membership in the ‘greater variety’ latent status. CONCLUSIONS: Supporting and encouraging physical activity in a variety of locations may improve physical activity levels in children.